Utilizing Metaverse Technology for the Preservation of Indigenous Houses in Southeast Sulawesi: A Study of Bajo, Tolaki, Muna, and Buton Cultural Heritage - Setiadi, Ahsan Hidayat; Syah, Andi Al Mustagfir (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
Abstract - Southeast Sulawesi, as one of the Provinces in Indonesia, has cultural artifacts that serve as diverse reflections of its culture and need to be preserved to ensure their continuity for future generations. There are four major indigenous ethnic groups in Southeast Sulawesi, namely Tolaki, Muna, Buton, Moronene, and Bajo, which represent the cultural diversity of the region. These ethnic groups have traditional houses that serve as cultural hubs, preserving cultural values and acting as iconic representations of the local culture in Southeast Sulawesi. The development of metaverse technology, a tangible proof of recent technological advancements, is known for its ability to create spatial environments in virtual reality. The urgency of this research arises from the lack of community interest in traditional houses, as evidenced by the eclectic and minimalist architectural designs, as well as the threat of extinction faced by traditional houses in Southeast Sulawesi. This study aims to preserve traditional houses in Southeast Sulawesi by integrating them with metaverse technology, enabling the transmission of cultural values to future generations. The research will employ a qualitative descriptive method. Additionally, this research aims to fill the gaps in previous studies by introducing metaverse technology as a groundbreaking innovation in addressing the threat of cultural artifact extinction in Southeast Sulawesi province. Keywords : Metaverse, Artifact, Preserving, Architectural.